A Model for Developing a Software-as-a-Service Platform for Universities: Analysis on Cloud Computing - A K M Faysol Mahmud Rusho (International Journal of Computer and Information System (IJCIS), 2026)
Cloud Computing is one of the most accessible and user-friendly storage services, as users do not need to construct a physical storage system. Using the internet, they can access this virtual storage for communication, data storage, publishing and testing, web development, file or data sharing, etc. As we are amid the fourth industrial revolution, all other sectors, including education, business, military, and health care, should be modernized to match its scope. The developed nation has already adopted cloud computing services for a more efficient and sustainable learning process in education 4.0. To be competitive in the global race, Bangladesh must adopt these services to improve its education system. Universities in the higher education sector can utilize cloud computing services effectively. Their research and user experience can be applied to other education sectors in Bangladesh. Leading universities already use cloud storage to store all of their teachers’ and students’ information. We have proposed a software-as-a-service (SaaS) platform for a university where students and faculties can use various software without installing or downloading. In addition, we have analyzed the opinions of students and faculty regarding a university’s cloud-based software service platform.